From Classroom to Boardroom: Insights from Higher Education Administrators in Turkey - Bayram, Arslan; Balyer, Aydin; Ozcan, Kenan; Kiraz, Zafer (SAGE PUBLICATIONS INC, 2025)
This study explores the experiences of academics in Turkey who transition from teaching roles to administrative positions in higher education (HE), with a focus on the implications of this shift for their academic productivity and social relations. Employing a qualitative phenomenological research design, semi-structured interviews were conducted with 25 academics who had undertaken such transitions. The data were analyzed with thematic analysis method. Thematic analysis of the data revealed that motivations for assuming administrative roles include financial incentives, the desire to contribute to institutional development, the pursuit of job security, and the application of theoretical knowledge in practice. However, the findings also suggest that the transition process often overlooks essential administrative competencies, qualifications, and leadership experience, potentially undermining institutional effectiveness. The study concludes by emphasizing the need for a more structured and competency-based transition process, incorporating leadership development, mentoring, strategic planning, and human resource support to ensure sustainable and effective academic leadership.
Keywords: administration; administrator; faculty; higher education; transition; LEADERS; MANAGERS; Social Sciences - Other Topics